6.2: Hybrid‐Type Temperature Sensors Using Thin‐Film Transistors: Characteristic Comparion of n, p., and Pin‐Type Transistors. Issue 1 (June 2015) - Kito, Katsuya; Hayashi, Hisashi; Kitajima, Shuhei; Matsuda, Tokiyoshi; Kimura, Mutsumi
Abstract : We have developed hybrid‐type temperature sensors using thinfilm transistors. Particularly in this presentation, we compare characteristics of those using n, p, and pin‐type transistors. For all types, temperature dependences of oscillation frequencies are confirmed, which indicates that they can be applied to temperature sensors.